Effects of Inline Skating Exercise on Symptoms, Executive Functions, and Motor Proficiency in Children With ADHD: A Randomized Controlled Trial - Chu-Yang Huang; Wen-Fan Chen; Chia-Liang Tsai; Po-Lin Chen; Po-Jen Hsu; Chien-Yu Pan (Occupational Therapy International)
Trial Registration: Australian New Zealand Registry of Clinical Trials: ACTRN12624000593538